I have the following problem...simplify the following:
7(2 - w) - (w - 3)
This is what im getting:
= 7(2 - w) - 1(w - 3)
= 14 - 7w - w - 3
= (7 - 1)w - (14 - 3)
= 6w - 11
Apparently the answer is actually; 17 - 2w
However i don't see where i am going wrong! I think it might be something to do with a wider problem when it comes to simplifying expressions. Generally speaking i am fine when there are + operators in the equation, but the more - operators the more difficulty I have.
Can someone point me in the right direction?